The impact of autonomy on the relationship between mentoring and entrepreneurial intentions among youth in Germany, Kenya, and Uganda - Mabunda Baluku, Martin; Matagi, Leonsio; Bantu, Edward; Otto, Kathleen (International Journal of Entrepreneurial Behavior & Research, 2018)
The purpose of this paper is to investigate how autonomy, moderated by employment status, impacts the relationship between entrepreneurial mentoring (EM) and entrepreneurial intentions (EI) among three countries (Germany, Kenya, and Uganda); as informed by both theory of planned behavior and self-determination theory. Design/methodology/approach – A convenient sample of 1,509 youth from Germany, Kenya, and Uganda consisting of final-year university students, wage-employed, and unemployed was identified and studied. A multi-group analysis was conducted to test for differences in the impact of EM and autonomy on EI. Findings – The findings indicate that mentoring and autonomy are positively correlated with EI. EM and intentions were lower among German participants than for the East African countries. The moderated moderation results revealed that EM is related to higher EI among students and the unemployed, and when individuals have higher levels of autonomy. Country-level analysis showed the effects of EM and autonomy are highest in Germany and lowest in Uganda. Practical implications – Mentoring and self-determination play an important role in the development of EI. Entrepreneurship mentors should specifically support their protégées to develop the ability to act autonomously as an important entrepreneurial competence. The results further indicate that effectiveness of EM varies according to employment status and among countries. This is particularly important for targeting and designing of EM interventions. EM resources should be applied to youth with high autonomy, who are in either in insecure wage employment or who have no jobs. Protégés with low levels of autonomy should be supported to appreciate autonomy and develop the ability for autonomous action. Future EI research should also examine the impact of the availability of attractive positions in wage employment; and the effects of the availability of social safety nets on the need for autonomy. Originality/value – A major challenge in EI research is the predominant focus on student populations. Using a multi-group analysis, the present paper tested for differences in the impact of EM and autonomy on EI. EM and EI were lower in German participants that in Kenyan and Ugandan participants. Whereas EM was generally positively correlated to EI, the moderated results showed that EM is related to higher EI among students and the unemployed, and when participants have higher autonomy. The study implies that EM and EI are highly correlated when participants need to work but have not or cannot find work or whey they do not need salaried employment to survive.
Keywords: Autonomy; Self-determination theory; Entrepreneurial intentions; Entrepreneurial education